2023
DOI: 10.3390/cancers15133279
|View full text |Cite
|
Sign up to set email alerts
|

B7-H3 in Pediatric Tumors: Far beyond Neuroblastoma

Abstract: B7-H3 is a 4Ig transmembrane protein that emerged as a tumor-associated antigen in neuroblastoma. It belongs to the B7 family, shows an immunoregulatory role toward NK and T cells, and, therefore, has been included in the growing family of immune checkpoints. Besides neuroblastoma, B7-H3 is expressed by many pediatric cancers including tumors of the central nervous system, sarcomas, and acute myeloid leukemia. In children, particularly those affected by solid tumors, the therapeutic protocols are aggressive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…This protein has been identified as a tumor-associated antigen in neuroblastoma, playing a crucial role in regulating immune responses towards natural killer and T cells. B7-H3 has been shown to be expressed in several types of pediatric cancers, such as tumors of the central nervous system, sarcomas, and acute myeloid leukemia [ 66 , 67 , 68 , 69 , 70 , 71 ]. Focusing on Gliomas: NCT01502917, a phase 1 clinical trial tested the safety and efficacy of 124 I-omburtamab, a monoclonal antibody labeled with 124 I targeting CD276 delivered by convection-enhanced delivery (CED) in patients with diffuse intrinsic pontine glioma (DIPG).…”
Section: Discussionmentioning
confidence: 99%
“…This protein has been identified as a tumor-associated antigen in neuroblastoma, playing a crucial role in regulating immune responses towards natural killer and T cells. B7-H3 has been shown to be expressed in several types of pediatric cancers, such as tumors of the central nervous system, sarcomas, and acute myeloid leukemia [ 66 , 67 , 68 , 69 , 70 , 71 ]. Focusing on Gliomas: NCT01502917, a phase 1 clinical trial tested the safety and efficacy of 124 I-omburtamab, a monoclonal antibody labeled with 124 I targeting CD276 delivered by convection-enhanced delivery (CED) in patients with diffuse intrinsic pontine glioma (DIPG).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been suggested that 4Ig rather than 2Ig can form dimers, 26 and increase the activation of AKT, JAK/STAT, HIF1α, NF‐κβ for cell proliferation 27 . The CAR‐T targets currently in use are also designed for 4Ig 28,29 . Although 4Ig is dominant in glioma tissues of the few glioma specimens we collected, 2Ig is specially expressed in glioma patients with malignant grade, hinting that designing CAR‐T targets for 2Ig may be a new strategy for high‐malignant glioma.…”
Section: Discussionmentioning
confidence: 99%
“…However, its crucial role in supporting H-CIC escape properties opens new promising perspectives to apply B7-H3-based therapies to control metastatic spread in selected NSCLC patient cohorts. [52][53][54] Author affiliations Acknowledgements We thank Professor Claudia Cantoni for the kind gift of NKp46-Fc and NKp44-Fc chimeric molecules. We thank Dr Eloisa Jantus Lewintre for kindly providing us NSCLC cell lines.…”
Section: Patient Consent For Publication Consent Obtained Directly Fr...mentioning
confidence: 99%